Performance of crossbreds of Polish Merino dams with F1 rams: Finnsheep x Polish Merino. B. Wool production of ewes - Osikowski, M.; Borys, B.; Osikowski, M. A. (Agricultural and Food Science, 1988)
The investigations were carried out on wool of 180 non-selected ewes with 25 % Finnsheep (F) genotype (F x PM x PM) and 51 purebred Polish Merino (PM) ewes as controls. The shearing took place at 23 months of age, after a year’s growth of fleece. Greasy and clean wool production, length and diameter of fibres as well as wool character evaluated by subjective appraisal were recorded. Crossbred ewes had a slightly lower greasy wool production (F x PM x PM—4.0 kg, PM—4.3 kg), but a much higher rendement (60.2 and 51.2 % resp.) and a little higher clean wool yield 2.38 versus 2.20 kg. Wool of the crossbreds was longer (11.4 vs 10.5cm) and coarser (24.8 vs 23.9 pm), but had a poorer character 14.9 vs 16.0 points.